Young People Who Use Drugs Views Toward the Power and Authority of Police Officers. (June 2022) - Greer, Alissa; Selfridge, Marion; Watson, Tara Marie; Macdonald, Scott; Pauly, Bernie
Many young people who use drugs are structurally vulnerable to policing powers given the ongoing criminalization of drug possession. Police authority limits and the expression of that authority may play a significant role in police encounters among young people who use drugs. This qualitative study explores the views of young people who use drugs toward police power and authority in their recent encounters with police officers. Interviews were conducted with 38 young people who recently used illegal drugs in British Columbia, Canada. We found five interrelated themes related to perceptions of police authority: (1) skepticism and distrust toward authority; (2) paternalism and authority over drug use; (3) officer use of force; (4) police as power-hungry; and (5) officers above the law. Participants described police authority as limitless, unpredictable, untethered, easily abused, and lacking accountability. Participants feared holding police officers accountable to power abuses in a criminal justice system that they saw as stacked against them. Moving forward, institutional reforms may consider and account for the expression, limits, and use of police authority among young people who use drugs and other structurally vulnerable communities.